(untitled) (Journal of School Administration Research and Development, 2022)
Job Satisfaction (JS) and Organizational Citizenship Behavior (OCB) are both considered crucial in an organizational setting. The association between JS and OCB promotes school effectiveness on multiple levels. With this consideration, this research aimed to examine the relationship between them, following a post-positivist philosophy with a cross-sectional survey design. The data collected randomly from 345 respondents were analyzed using correlation and regression analysis and finally interpreted with the social capital and social exchange theory. The results confirmed the positive relationship between job satisfaction and organizational citizenship behavior, which further supports teachers’ high job performances and work productivity. Likewise, the relationship between job satisfaction and organizational citizenship behavior supports organizational commitment and effectiveness among teachers to promote better educational achievement in schools.